Urban Phytoremediation: A Nature-Based Solution for Environmental Reclamation and Sustainability - Luca Di Stasio; Annamaria Gentile; Dario Nicola Tangredi; Paolo Piccolo; Gianmaria Oliva; Giovanni Vigliotta; Angela Cicatelli; Francesco Guarino; Werther Guidi Nissim; Massimo Labra; Stefano Castiglione (Plants, 2025)
Starting from the Industrial Revolution in the 18th century to date, urban areas have faced increasing environmental challenges due to the diffusion of harmful substances, resulting from vehicular traffic, the activities of different industries, waste, and building construction, etc. These pollutants are dangerous, since they pose a threat to both the environment and human health. Phytoremediation is an environmentally friendly and low-cost technique that uses plants and their associated microorganisms to clean-up contaminated sites. In this review, we explore its main applications in urban settings. Specifically, we investigate how phytoremediation works, highlighting the most effective plants for its success in a city context. Moreover, we also describe the main factors influencing its effectiveness, such as soil, climate, and pollutants. In this regard, several case studies, conducted worldwide, have reported on how phytoremediation can successfully reclaim contaminated areas, transforming them into reusable city green spaces, with reduced costs compared to traditional remediation techniques (e.g., soil replacement, soil washing, etc.). Moreover, by integrating it into urban planning, cities can address environmental pollution, while promoting biodiversity, enhancing the landscape, and increasing its social acceptance. This nature-based solution offers a practical path toward more sustainable and resilient urban environments, especially in regard to the climate change framework.